2020
DOI: 10.31579/2693-7247/020
|View full text |Cite
|
Sign up to set email alerts
|

A short communication nutritional observation study

Abstract: Obesity is the most prevalent nutritional dysfunction in society and the vital risk determinant for several relevant disorders. The first step of obesity assessment is calculated anthropometric measures and, secondly, measure biological and nutritional profiles. The current purpose is to investigate the relationship between BMI with biochemical profile, Vitamin B12, Fe, and cortisol in the volunteer’s population. There is an appositively connection between body mass index (BMI) with cortisol, liver and kidne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…The relationship between stress and heavy metals was confirmed in a previous publication. The investigation reported that there was a positive relationship between the measured heavy metals and cortisol hormone levels in plasma [ 77 , 78 ], which agrees with the current results, as this position also represents the interaction with cortisol and receptor proteins; moreover, the current results report the binding energy among Cr, Cd, Pb, and Al and cortisol, which may also lead to increases in stress and inflammatory markers and enzymes, as mentioned in our previous publications [ 79 , 80 , 81 , 82 ]. Also, other previous publication report relationships among heavy metals and COX-2 and other inflammatory markers, such as LOX and increased oxidative stress [ 61 , 83 , 84 , 85 , 86 ], and this agrees with our current results, where there is a high binding affinity between COX-2 and LOX.…”
Section: Discussionsupporting
confidence: 92%
“…The relationship between stress and heavy metals was confirmed in a previous publication. The investigation reported that there was a positive relationship between the measured heavy metals and cortisol hormone levels in plasma [ 77 , 78 ], which agrees with the current results, as this position also represents the interaction with cortisol and receptor proteins; moreover, the current results report the binding energy among Cr, Cd, Pb, and Al and cortisol, which may also lead to increases in stress and inflammatory markers and enzymes, as mentioned in our previous publications [ 79 , 80 , 81 , 82 ]. Also, other previous publication report relationships among heavy metals and COX-2 and other inflammatory markers, such as LOX and increased oxidative stress [ 61 , 83 , 84 , 85 , 86 ], and this agrees with our current results, where there is a high binding affinity between COX-2 and LOX.…”
Section: Discussionsupporting
confidence: 92%